Pengaruh Eksposur Sosial Media dan Fear Of Missing Out (FOMO) Terhadap Keputusan Pembelian Pada Two Days Coffe & Space Garut - Hilman Rismanto; Ahmad Salman Sya’ban; Rido Muhamad Robani; Fatih Ulayya; Nauval Putra Ridha Rabbani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of social media exposure and Fear of Missing Out (FOMO) on purchase decisions at Two Days Coffee & Space Garut. The research employed a quantitative approach using a survey method by distributing questionnaires to 94 respondents. Data were analyzed using SPSS version 25 through validity, reliability, and multiple regression tests. The results indicate that social media exposure and FOMO have an influence on consumers’ purchase decisions. All research instruments were proven to be valid and reliable, indicating that they are appropriate for use in this study.